Flutuação na segmentação de palavras: relações entre constituintes prosódicos e convenções ortográficas na escrita infantil - Jurado Filho, Lourenço Chacon [UNESP] (2013)
In this paper, we analyzed situations where (a) one vocabular structure showed in two diﬀerent ways in the same text or (b) had erasures. These structures ﬂuctuations were extracted from texts written by children that, when the registers were done, were second graders of elementary school. Concerning the results, we veriﬁed: (1) that more than one prosodic constituent showed in the basis of ﬂuctuation of vocabulary structures; and (2) that at least one of the limits of orthographic words was maintained in ﬂuctuation structures. These results point to the recuperation done by writers with information they have access due to their insertion in (1) oral practices and (2) literacy practices.